Effects of Aluminum Foam Filling on Compressive Strength and Energy Absorption of Metallic Y-Shape Cored Sandwich Panel - Leilei Yan; Pengbo Su; Yagang Han; Bin Han (Metals, 2020)
The design of lightweight sandwich structures with high specific strength and energy absorption capability is valuable for weight sensitive applications. A novel all-metallic foam-filled Y-shape cored sandwich panel was designed and fabricated by using aluminum foam as filling material to prevent core member buckling. Experimental and numerical investigation of out-of-plane compressive loading was carried out on aluminum foam-filled Y-shape sandwich panels to study their compressive properties as well as on empty panels for comparison. The results show that due to aluminum foam filling, the specific structural stiffness, strength, and energy absorption of the Y-shape cored sandwich panel increased noticeably. For the foam-filled panel, aluminum foam can supply sufficient lateral support to the corrugated core and vertical leg of the Y-shaped core and causes a much more complicated deformation mode, which cannot occur in the empty panel. The complicated deformation mode leads to an obvious coupling effect, with the stress–strain curve of the foam-filled panel much higher than those of the empty panel and aluminum foam, which were tested separately. Metallic foam filling is an effective method to increase the specific strength and energy absorption of sandwich structures with lattice cores, making it competitive in load carrying and energy absorption applications.